Tax Rate, Intangible Assets, Bonus Mechanism, Leverage on Transfer Pricing in Technology Companies in 2019-2023 - Imelda Imelda; Regina Jansen Arsjah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Transfer pricing has emerged as a critical issue in Indonesia's technology sector, driven by rapid growth (2019–2023) and regulatory scrutiny under BEPS, with firms leveraging intangible assets, tax disparities to optimize profits. This study examines these dynamics through Agency Theory (Jensen & Meckling, 1976) and Institutional Theory (DiMaggio & Powell, 1983), revealing how managerial incentives and external pressures shape transfer pricing strategies. This study used existing data from company annual reports collected through documentation methods, using descriptive statistics to summarize the data and inferential statistics with the Seemingly Unrelated Regression (SUR) model in EVIEWS to test the hypotheses. The research reveals that tax rate, intangible assets, and leverage do not significantly influence transfer pricing decisions, indicating that these factors may not be the primary drivers of transfer pricing strategies. Conversely, bonus mechanisms significantly affect transfer pricing, highlighting the importance of managerial incentives in shaping corporate tax practices.